The Impact of Gender on Extremism among Refugees in Erbil Camp - Aljunaibi, Mohamed; Al-Othman, Hussain; Alomosh , Ahmad (Al-Adab Journal, 2024)
The study seeks to identify the impact of gender on the concept of extremism among refugees in the Erbil refugee camp in Iraq, by measuring the extent of some concepts in extremism in several areas, including (the causes of extremism, the consequences of extremism, addressing extremism). A questionnaire was designed for male and female refugees and over 18 years of age, and this questionnaire was applied to 300 people from the camp and from all educational groups and in a set of variables (180 males and 120 females) by using the purposeful non-probability sampling method. And by analyzing the results of the study, the effect of gender was shown and the extent of the concept and definition of extremism among males and females was measured, and it was found through the study that there are statistical indications that differ in the concept between males and females. Understand the concepts of extremism and what are its effects and causes. Several recommendations have been included that contribute to finding successful methods for dealing with extremism.